Pathophysiology and inhibition of cholesteryl ester transfer protein for prevention of cardiovascular diseases: An update. Issue 7 (July 2021) - Banerjee, Surojit; De, Abhijit
Highlights: Cholesteryl Ester Transfer Protein is an enzyme, entailed in cholesterol metabolism. Different CETP inhibitors were in clinical trials, maximum of which were failed. Despite of having efficiency clinical trial (REVEAL) of anacetrapib was stopped. Monotherapy and combination therapy of these drugs shown significant differences. CETP inhibitors only work in patients having a rare genotype and a rare gene. Abstract: The enzyme cholesteryl ester transfer protein (CETP), involved in cholesterol metabolism and transportation, is one of the main causes of cardiovascular (CV) disease (CVD). When the CETP concentration is decreased by CETP inhibitors (e.g., anacetrapib, torcetrapib, obicetrapib, etc.), high-density lipoprotein (HDL) particles are formed and low-density lipoprotein (LDL) is decreased along with cholesterol transportation alteration, which reduces the development of atherosclerosis. Here, we discuss the role of CETP inhibitors in reducing well-known 'bad' cholesterols and the current status of trials of different CETP inhibitors, their adverse effects, and limitations, as well as the pathophysiology of CETP.